2020
DOI: 10.3390/nano10102041
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose Bio-Based Composites for Food Packaging

Abstract: The food industry is increasingly demanding advanced and eco-friendly sustainable packaging materials with improved physical, mechanical and barrier properties. The currently used materials are synthetic and non-degradable, therefore raising environmental concerns. Consequently, research efforts have been made in recent years towards the development of bio-based sustainable packaging materials. In this review, the potential of nanocelluloses as nanofillers or as coatings for the development of bio-based nanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 150 publications
0
83
0
1
Order By: Relevance
“…Extensive research has been reported with petroleum based polymer matrices, though far fewer studies have been carried out with biobased polymer matrices. 12,13 More importantly, the understanding of molecular structures and interactions within biobased polymers is very limited, as these polymers oen possess complicated architectures and vary from different parent sources. [14][15][16][17][18] The fundamental study and systematic comparison of nanoparticle assembly structures within different biopolymers are needed to provide insight on the interactions and assembly mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been reported with petroleum based polymer matrices, though far fewer studies have been carried out with biobased polymer matrices. 12,13 More importantly, the understanding of molecular structures and interactions within biobased polymers is very limited, as these polymers oen possess complicated architectures and vary from different parent sources. [14][15][16][17][18] The fundamental study and systematic comparison of nanoparticle assembly structures within different biopolymers are needed to provide insight on the interactions and assembly mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Although cellulose is mainly used in the pulp and paper industry, it has been exploited, along with its derivatives (e.g., cellulose acetate (CA), carboxymethylcellulose (CMC), and ethylcellulose (EC)) and nanoforms (i.e., cellulose nanocrystals (CNCs), cellulose nanofibrils (CNFs) and bacterial nanocellulose (BNC) [ 36 , 48 , 49 ]), for other purposes, including textiles [ 50 ], fuel cells [ 51 , 52 , 53 ], electronics [ 54 , 55 ], water remediation [ 56 , 57 , 58 ], food packaging [ 59 , 60 , 61 ], cosmetics [ 62 , 63 ], drug delivery [ 64 , 65 ], cell and tissue cultures [ 66 , 67 ], just to mention some examples. In order to be applied in these multiple domains, cellulose needs to be extracted from biomass resources by conventional technologies (e.g., kraft pulping) or innovative methodologies (e.g., extraction with ionic liquids (ILs) or deep eutectic solvents (DES)) [ 68 , 69 , 70 , 71 ] or produced in its pure form by non-pathogenic bacteria (e.g., Komagataeibacter ) [ 63 , 72 , 73 ].…”
Section: Cellulose Fundamentalsmentioning
confidence: 99%
“…Regardless of the type of nanomaterial, the process conditions are essential to achieve the dispersion of the nanomaterial in the main matrix. [ 74 ] Several methods are mentioned in the literature including solvent casting, melt processing, and layer‐by‐layer assembly.…”
Section: Process Of Nanomaterials Addition To Starch‐based Packagingmentioning
confidence: 99%